REGULATING DIRECTORS’ DUTIES AND SOUTH AFRICAN COMPANY LAW REFORM - Michele Havenga (Obiter, 2022)
It has for some time been apparent that South African company law needs to be comprehensively rewritten. Far-reaching changes have occurred since the previous revision that led to the Companies Act of 1973. Amongst other factors, there is a new political, social and economic dispensation, and our company law should, as far as is feasible, be harmonized with the laws of international investors and other Southern African states. The policy document issued in June 2004 by the Department of Trade and Industry on the reform of corporate law, and their structured approach to the reform process, should therefore be welcomed. The inevitable influence of the Constitution and related legislation promoting its provisions, are considered in this article with specific regard to the proposals contained in the policy document on directors and their duties. The Promotion of Access to Information Act of 2000 and the Broad-based Black Economic Empowerment Act of 2003, which serve as examples of such related legislation, are considered, as are the suggestions contained in the policy document with regard to the structure of the board and on the possible codification of directors’ duties. The new Companies Act should ensure that directors will be held accountable for their actions and that the interests of interest groups other than shareholders may also be considered in corporate decision-making. Existing mechanisms provided for in our law should not be in conflict with the provisions of the new Act. But unnecessary amendments are undesirable and do not promote legal certainty. It should also be kept in mind that social change might be better advanced by other means than in corporate legislation. Furthermore, specific aspects in other jurisdictions should not be incorporated in our law without a proper understanding of the broader context of the corporate laws of those jurisdictions. The DTI’s quite ambitious reform programme envisages draft legislation by 2006.